Chatbot Adoption Framework for Real-Time Customer Care Support - Geoffrey Nyongesa; Kelvin Omieno; Daniel Otanga (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2025)
As sectors increasingly digitize, adopting artificial intelligence (AI) chatbots to supplement human customer service is becoming essential. However, Kenyan telecom companies lack well-formulated rules for implementing these systems. This study proposes an adoption framework for deploying AI chatbots in the telecommunications sector. By assessing the current level of chatbot installation in Kenya and reviewing previous technology adoption models, primary metrics for chatbot dissemination were identified. A mixed-methods approach was used, collecting quantitative and qualitative data via questionnaires and interviews with AI experts from Safaricom PLC and the Communications Authority of Kenya using the Delphi method. The resulting framework provides crucial guidelines for telecommunication companies planning to adopt AI chatbots for real-time customer care support.